Pengelolaan Anemia dalam Kehamilan dengan Manajemen Terpadu oleh Dokter Keluarga - [Tidak Terdaftar] (Fak. Kedokteran UMY, 1900)
Pengelolaan Anemia dalam Kehamilan dengan Manajemen Terpadu oleh Dokter Kelu